Sonifying the Scene: re-framing and manipulating meaning through audio augmentation - Chamberlain, Alan; Hazzard, Adrian (2015)
Digital locative music technologies are transforming the ways in which we are able to manipulate and re-frame the meaning of architecture, landscape and art. In this note we explore and outline some of the key features that are associated with this. Defining the future possibilities and challenges that we have identified through our re-search in the area. Our work is supported by examples and critically assesses the relationship between physical and aural presence, examining the manipulation and re-framing of meaning through audio augmentation. “Is Space Audible?” [7].